2019
DOI: 10.3390/ma12132151
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Engineering Properties of Calcium Sulfoaluminate Cement-based Concretes Reinforced with Different Types of Fibers

Abstract: Calcium sulfoaluminate (CSA) cement has recently gained increased attention due to its lower amount of CO2 emissions, as compared to that of the ordinary Portland cement (OPC). This paper evaluates the impact of different types of fibers on the engineering features of CSA-based concretes at different water-cement ratios of 0.35 and 0.28. In this study, metallic fibers including double hooked-end steel fibers and hooked-end steel fibers, and non-metallic fibers (i.e., polyvinyl alcohol (PVA) fibers) were utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 42 publications
(44 reference statements)
1
9
0
Order By: Relevance
“…In the last decades, significant research has been conducted on the application of nanomaterials and innovative materials for improving the structural, mechanical and durability characteristics of cement [1][2][3][4][5][6][7][8][9] and concrete [10][11][12][13][14][15][16][17] materials. Since self-compacting concrete (SCC) is increasingly used in construction of both conventional and advanced structures, 18,19 the enhancement of its properties can be highly beneficial, in particular, in terms of sustainable development in the construction industry.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, significant research has been conducted on the application of nanomaterials and innovative materials for improving the structural, mechanical and durability characteristics of cement [1][2][3][4][5][6][7][8][9] and concrete [10][11][12][13][14][15][16][17] materials. Since self-compacting concrete (SCC) is increasingly used in construction of both conventional and advanced structures, 18,19 the enhancement of its properties can be highly beneficial, in particular, in terms of sustainable development in the construction industry.…”
Section: Introductionmentioning
confidence: 99%
“…Steel fiber is one of the most popularly used fibers to enhance the mechanical strength of concrete [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Nguyen et al indicated that the effects of rubber aggregates and fiber reinforcement could result in better cracking resistance for cement mortar [28].…”
Section: Introductionmentioning
confidence: 99%
“…That provision specifically refers to frames, checking that lateral loads will cause yielding in beams rather than in columns. It is intended to avoid hinge formation in multiple columns at the same level, which could cause story collapse, as well as to ensure an overall dissipative and ductile behavior that spreads inelastic response over several stories [21][22][23][24].…”
Section: Capacity Design and Strength Hierarchy: Strong Column-weak Beam Rulementioning
confidence: 99%